2011
DOI: 10.1038/ismej.2011.83
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and diversification of Pseudomonas aeruginosa in the paranasal sinuses of cystic fibrosis children have implications for chronic lung infection

Abstract: The opportunistic pathogen Pseudomonas aeruginosa is a frequent colonizer of the airways of patients suffering from cystic fibrosis (CF). Depending on early treatment regimens, the colonization will, with high probability, develop into chronic infections sooner or later, and it is important to establish under which conditions the switch to chronic infection takes place. In association with a recently established sinus surgery treatment program for CF patients at the Copenhagen CF Center, colonization of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
178
5
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 204 publications
(209 citation statements)
references
References 62 publications
15
178
5
11
Order By: Relevance
“…1), which contrasts the frequent observations of phenotypic heterogeneity in clonal P. aeruginosa populations within the same CF respiratory specimen (22)(23)(24)(25)(26) and evolutionary theory predicting enhanced diversification and specializing adaptation in spatially structured environments (27,28). However, the evolution of the mucA DK2 algT…”
Section: Discussionmentioning
confidence: 90%
“…1), which contrasts the frequent observations of phenotypic heterogeneity in clonal P. aeruginosa populations within the same CF respiratory specimen (22)(23)(24)(25)(26) and evolutionary theory predicting enhanced diversification and specializing adaptation in spatially structured environments (27,28). However, the evolution of the mucA DK2 algT…”
Section: Discussionmentioning
confidence: 90%
“…Also, recent analyses showed that traditional culture methods (i.e., isolating a small number of morphologically different bacterial colonies from each culture) frequently underrepresent the P. aeruginosa diversity in individual samples of CF respiratory secretions during chronic infection with respect to several phenotypes (44)(45)(46)(47); therefore, even the large isolate collection in this study likely undersampled the phenotypic diversity of P. aeruginosa in each subject. Similarly, it is possible that sputum and OP specimens are not sufficiently sensitive to reflect the earliest stages of infection, whether of the lower or upper airways (48,49), potentially explaining the observed high frequency in our "early" isolates of phenotypes commonly associated with adaptation.…”
Section: Discussionmentioning
confidence: 98%
“…12 In the early stages of lung colonization, the migration of pathogens may mainly occur in a downward direction, with the sinuses as a primary focus. 12 Several studies found concordance between upper and lower airway bacteriology in both patients with CF [13][14][15][16][17] and those with PCD. 11 Although the pattern of bacterial flora in the lower airways has been extensively studied, the upper airways have drawn limited attention.…”
Section: Ystic Fibrosis (Cf) Is An Autosomal Recessive Genetic Diseasementioning
confidence: 99%